Sexuality-Related Factors and Quality of Life Among Reproductive-Aged Married Female Migrant Workers: A Cross-Sectional Study in Southern China - Li, Bingbing (Sex Med, 2019)
INTRODUCTION: Sexuality is a critical part of overall well-being. However, until now, studies on women’s health related to the effect of sexuality on physical and psychosocial outcomes have been seriously ignored, especially the health-related quality of life (QOL) of reproductive-aged married female migrant workers. AIM: To analyze the associations between sexuality-related factors and QOL and explore the independent contributions of sexuality-related factors to QOL in this population group in southern China. METHODS: In this cross-sectional survey, 609 Chinese married female migrant workers aged 19–49 years were studied. Clustered multiple linear regressions were used to analyze the associations between sexuality-related variables and QOL. OUTCOMES: QOL was measured using the Short Form (SF-36) Healthy Survey. Details of the participants (sociodemographic, health-related and sexuality-related factors) were obtained. RESULTS: Approximately 10.0% of respondents always felt a lack of sexual interest and lubrication difficulties, and 37.5% of respondents seldom or never experienced sexual satisfaction. Multiple regression analyses revealed that women who never felt lubrication difficulties obtained higher role physical, bodily pain, general health, and physical component summary scores in physical domains and higher vitality (VT), mental health (MH), and mental component summary (MCS) scores in mental domains compared with those who always felt lubrication difficulties. Compared with those who always experienced sexual satisfaction, women who never experienced sexual satisfaction had relatively lower role physical, bodily pain, and general health scores in physical domains, and women who never or seldom experienced sexual satisfaction had lower VT, MH, and MCS scores in mental domains. The independent contributions of sexuality-related factors in mental domains (VT, MH, and MCS) accounted for 50.0%, 52.4%, and 39.5%, respectively; more than that of all sociodemographic and health-related variables in the VT and MH domains. CONCLUSIONS: Sexuality-related factors (lubrication difficulties and sexual satisfaction) were significant independent determinants of QOL among reproductive-aged Chinese married female migrant workers, especially in mental domains. Li BB, Liu N, Li B, et al. Sexuality-Related Factors and Quality of Life Among Reproductive-Aged Married Female Migrant Workers: A Cross-Sectional Study in Southern China. Sex Med 2019;7:384–395.